CONTENT CHARACTERISTICS OF THE "SUBJECT FIELD" OF DISCRIMINATORY ATTITUDES - Elena E Bocharova (Peoples' Friendship University of Russia (RUDN University), 2018)
The aim of the research presented in the article is the theoretical and empirical study of the content of the subject field of discriminatory attitudes. The study is based on the sample ( N = 168), the average age is 27.63 years, the sample is predominantly female (78.6%). The following approaches were used in the study: "Scale of basic beliefs" by R. Janoff-Bullman adapted by M.A. Padun and A.V. Kotelnikova (Padun, Kotelnikova, 2008); the characteristics of the discriminatory attitudes and attributes were collected using a specifically developed questionnaire. The ratio of the expressiveness of the fundamental beliefs was analysed in the study. It generally indicates the subjects' beliefs in the benevolence of the surrounding world, in the value of their own Self against the background of doubting the world's justice and the ability to control life events. The fact of the situational manifestation of the discriminatory attitudes is recorded. The content characteristics of the discriminatory attributes of the cross-group discrimination are established, including " Unusual behaviour ", " That he/she does something worse than I do ", " That he/she does something better than I do ", the content of which is described as " Danger to people ", " He/she does everything badly ", " Disingenuity " (respectively). The content characteristics of "the subject field" of discriminatory attitudes are identified including the unusual behaviour of the Others different from the generally accepted social norms, the supremacy of "my group", adherence to a different culture or subculture. A significant "contribution" to the content of discriminatory attitudes - the fundamental belief "conviction of the need for control" - has been revealed in relation to the "unusual behaviour" described by the subjects as socially dangerous. The applied aspect of the investigated problem can be realized in the development of the preventive programs to reduce the risk of discriminatory behavior.